THE EFFECT OF PALM OIL SHELL BIOCAR AND P AND K FERTILIZER ON THE GROWTH AND PRODUCTION OF SOYBEAN PLANTS (Glycine max) - Ichpan Zulfansyah; Fuad; Nurhayati; Nor Azma Yusuf (RADJA PUBLIKA, 2024)
This study aimed to determine the effect of palm kernel shell biochar and phosphorus (P) and potassium (K) fertilizers on the growth and production of soybean (Glycine max) plants. The study was conducted at the Experimental Field of the Faculty of Agriculture, Al Washliyah University, Medan, using a factorial Randomized Block Design (RBD) with two treatment factors, namely biochar (B0, B1, B2, B3) and P and K fertilizers (P0, P1, P2, P3). The parameters observed included plant height, number of pods, seed weight, and other production parameters. The results showed that both biochar and P and K fertilizers independently had a very significant effect on all growth and yield parameters of soybean. The best treatment was the combination of B3 (6 kg/plot) and P3 (24 g P + 44 g K), which produced the highest average in plant height, number of pods, and seed weight. However, the interaction between biochar and P and K fertilizers did not show a significant effect on the growth and production of soybean plants. This study indicates that the appropriate application of biochar and P and K fertilizers can significantly increase soybean growth and yield, although the combination did not show a statistically significant synergistic effect. These findings support the use of biochar as an alternative organic material in sustainable agricultural systems.